Global longitudinal strain as a marker for systolic function in patients with pheochromocytomas. Issue 10 (October 2020) - Elenkova, Atanaska; Shabani, Rabhat; Kinova, Elena; Vasilev, Vladimir; Goudev, Assen; Zacharieva, Sabina
Abstract : Cardiomyopathy is a frequent complication of pheochromocytoma, and echocardiography is the most accessible method for its evaluation. The objective of this study was to assess the clinical significance of classical and novel echocardiographic parameters of cardiac function in 24 patients with pheochromocytomas (PPGL) compared to 24 subjects with essential hypertension (EH). Fourteen PPGL patients were reassessed after successful surgery. Left ventricular hypertrophy was four times more prevalent in patients with PPGL vs EH (75% vs 17%; P = 0.00005). Left ventricular mass index (LVMi) significantly correlated with urine metanephrine (MN) ( rs = 0.452, P = 0.00127) and normetanephrine (NMN) ( rs = 0.484, P = 0.00049). Ejection fraction (EF) and endocardial fractional shortening (EFS) were normal in all participants and did not correlate with urine metanephrines. Global longitudinal strain (GLS) was significantly lower in PPGL compared to EH group (−16.54 ± 1.83 vs −19.43 ± 2.19; P < 0.00001) and revealed a moderate significant positive correlations with age ( rs = 0.489; P = 0.015), LVMi ( rs = 0.576, P < 0.0001), MN ( rs = 0.502, P = 0.00028) and NMN ( rs = 0.580, P < 0.0001). Relative wall thickness (RWT) showed a strong positive correlation with urine MN ( rs = 0.559, P < 0.0001) and NMN ( rs = 0.689, P < 0.00001). Markedly decreased LVMi (118.2 ± 26.9 vs 102.9 ± 22.3; P = 0.007) and significant improvement in GLS (−16.64 ± 1.49 vs −19.57 ± 1.28; P < 0.001) was observed after surgery. ΔGLS depended significantly on the follow-up duration. In conclusion, classical echocardiographic parameters usually used for assessment of systolic cardiac function are not reliable tests in pheochromocytoma patients. Instead, GLS seems to be a better predictor for the severity and the reversibility of catecholamine-induced myocardial function damage in these subjects. RWT should be measured routinely as an early indicator of cardiac remodeling.